PJMHS 2022
DOI: 10.53350/pjmhs22167839
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Outpatient Primary Hypothyroidism in Riyadh

Abstract: Objective: To estimate the Primary Hypothyroidism and to study its effects on the Quality of Life of those patients. Study design: It was a Cross-Sectional Study done using random sampling. Sample size: 463 patients Duration and location of the study: It was done between December 2018 and December 2019 in outpatient clinics of a tertiary care hospital in Riyadh. Study tool: The quality of life of these patients was assessed by World Health Organization (WHO) Health Survey 36-Item Short Form (SF-36) questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…No population-wide studies of hypothyroidism have been conducted in Saudi Arabia. However, in a cross-sectional study conducted in outpatient clinics of a tertiary care hospital in Riyadh that included 463 patients between December 2018 and December 2019, primary hypothyroidism prevalence was found to be 47.8% [ 11 ]. Furthermore, cross-sectional research from Riyadh found a prevalence of subclinical hypothyroidism of 10% among people visiting a primary care clinic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…No population-wide studies of hypothyroidism have been conducted in Saudi Arabia. However, in a cross-sectional study conducted in outpatient clinics of a tertiary care hospital in Riyadh that included 463 patients between December 2018 and December 2019, primary hypothyroidism prevalence was found to be 47.8% [ 11 ]. Furthermore, cross-sectional research from Riyadh found a prevalence of subclinical hypothyroidism of 10% among people visiting a primary care clinic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%